Los estereotipos y sus consecuencias en el proceso de aprendizaje escolar de los niños/niñas en la escuela fiscal mixta José Miguel Jarrin Maldonado del recinto la Chongona, parroquia San Luis de Pambil, canton Guaranda provincia de Bolivar, periodo 2011 -2012 - Calero Maldonado, Sulema Mercedes (2012)
My investigation work is made up of the topic that he/she says this way: The stereotypes and their consequences in the process of school learning of the niños/niñas in the mixed fiscal school José Miguel Jarrín Maldonado of the enclosure the chongona, parish san Pambil Luis, canton Guaranda county of Bolívar, period 2011 -2012, he/she was carried out Then with the objective of eliminating the stereotypes that cause consequences in the process of school learning of the niños/niñas in the mixed fiscal school José Miguel Jarrín Maldonado we have the introductory part, in which thinks about, the antecedents, the problem, the justification, objectives, hypothesis and the operacionalización of variables; what corresponds to the general presentation of the work. This grade work is divided in 4 chapters that are structured in the following way. The chapter I is designed by the Theoretical Marco, which is broken into fragments in four parts that are: Marco Scientist, Legal Marco, Conceptual Marco and Marco Referencial, in the Marco Scientist ideas are captured, different authors' thoughts with concerning In the chapter II that are the methodological strategies are about the investigation types, of the techniques and instruments for the gathering of data, on the universe and the studied population's sample, of the prosecution of the received data and the methods used in our investigation In the chapter III the results obtained after having carried out the survey to the Students and Professors of the School are captured graphically, it joins with their respective hypothesis confirmation their conclusions and recommendations. The chapter IV are about the proposal that we present for, to develop a seminar shop directed to educational, family parents and students of the mixed fiscal school José Miguel Jarrín Maldonado of the enclosure the chongona, parish san Luis of Pambil.